USE OF THE SCIENTIFIC AND PEDAGOGICAL HERITAGE OF ABU BAKR VARROQ TERMEZI IN THE SPIRITUAL AND MORAL EDUCATION OF STUDENTS - Asroridin Samiyev Sayfidinovich; Surayyo Samiyeva Oripovna (Scholar Express Journal, 2022)
The article discusses the negative changes in the behavior of students as a result of the integration of religions, national values, traditions, languages and cultures under the influence of globalization due to the high level of development of science and technology. the use of national-spiritual heritage in the educational process of students is one of the most pressing problems of today and recommendations are given with reasonable ideas for its solution.
Keywords: Science; spirituality; enlightenment; ethics